COMPARATIVE EVALUATION OF SURGICAL METHODS FOR HIATAL HERNIA TREATMENT: EXPERT PERSPECTIVES AND EVIDENCE-BASED REVIEW - Oktyabr R. Teshaev,; Akhmadjon B. Babajonov ,; Ilkhom B. Khayitov ,; Diana I. Yugay, (Central Asian Journal of Medicine, 2025)
Recent advances in surgical techniques for hiatal hernia repair have fundamentally transformed treatment approaches, leading to diverse surgical strategies and ongoing debates about optimal methods. This comprehensive review analyzes current surgical approaches through systematic evaluation of expert perspectives from 2014-2024, examining outcomes across laparoscopic, robotic, and open surgical techniques. The analysis encompasses multiple key aspects: surgical approach selection criteria, technical considerations, mesh usage protocols, and both short-term and long-term outcome assessments. Recent studies demonstrate evolving trends toward minimally invasive approaches while acknowledging the continued importance of traditional techniques in specific clinical scenarios. Analysis of surgical outcomes reveals varying success rates: 85-95% for primary repairs and 70-85% for complex cases, with recurrence rates ranging from 12-25% depending on technique and patient factors. Emerging technologies, particularly robotic platforms and advanced imaging systems, show promise in improving surgical precision and outcomes. The review highlights areas of expert consensus regarding individualized approach selection, standardized preoperative evaluation protocols, and the critical importance of technical precision. Additionally, it explores ongoing controversies in surgical technique selection, mesh reinforcement strategies, and emerging technological applications, particularly in complex cases involving giant hernias and revision surgeries.